An investigation of improving validity in upper limb measurements for people with tetraplegia using construct specification equations - Johanna Wangdell; Leslie Pendrill; Jennifer A. Dunn; Bridget Hill; Jeanette Melin (Scientific Reports)
Abstract The aim of this paper is two-fold: to investigate development of a Construct Specification Equation (CSE) for UL task difficulty, , and a CSE for person UL ability, , in support of the validity of these two constructs. Measurements of UL task difficulty, , and person UL ability, were derived from applying the Rasch model on the Tetraplegia Upper Limb Activity Questionnaire (TUAQ). The formulations of CSEs as explanations of the two constructs were done using Principal Component Regression (PCR). The CSE for UL task difficulty, , was to a large degree explained by the number of joints involved and the CSE for person UL ability, , was dominated by grasp-related variables. Pearson coefficients of 0.94 and 0.73 were obtained between UL task difficulty and UL person ability from the CSE, respectively, when correlated with each empirical measure. The present work has both explored and extended the methodology for using more qualitative explanatory variables. Specifically, for UL measurements for people with tetraplegia a good CSE for task difficulty, , supports the validity of TUAQ when measuring person UL ability. Additionally, the CSE formulated for person ability, , can be used both for validation purposes as well as a clinical tool.